2010
DOI: 10.4103/0974-2727.72216
|View full text |Cite
|
Sign up to set email alerts
|

Incisional Endometriosis: Diagnosed by Fine Needle Aspiration Cytology

Abstract: Incisional endometriosis (IE) is a rare entity reported in 0.03–1.08% of women following obstetric or gynecologic surgeries. Most cases reported in literature have appeared after cesarean sections and were often clinically mistaken for hernia, abscess, suture granuloma or lipoma. We hereby report a case of IE following a second trimester hysterotomy, which was diagnosed by fine needle aspiration cytology (FNAC). Our patient was 26 years old, presenting with a mass over anterior abdominal wall, associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Endometriosis occurring in a surgical scar is called incisional endometriosis or scar endometriosis. 3 The first case of scar endometriosis was reported by Meyer in 1903. 4 Blanco et al reported 12 cases of scar endometriosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endometriosis occurring in a surgical scar is called incisional endometriosis or scar endometriosis. 3 The first case of scar endometriosis was reported by Meyer in 1903. 4 Blanco et al reported 12 cases of scar endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of any two of the three components is required for the diagnosis of endometriosis. 3 Medical management with oral contraceptive pill, progestogens and gonadotropin releasing hormone analogues provide alleviation of symptoms, but recurrence after cessation of therapy is common. Wide surgical excision with at least 1 cm margin on all sides is the treatment of choice.…”
Section: Discussionmentioning
confidence: 99%
“…FNAC can confirm the diagnosis by demonstrating epithelial cell, stromal cells and hemosiderin-laden macrophages. [3] MRI is gold standard, which can detect small lesions and confirm its vascularity.…”
Section: Discussionmentioning
confidence: 99%
“…The true incidence of endometriosis is not known, but it is believed that 10-15% of all women in their reproductive age develop endometriosis and 25-35% of all women who are infertile have endometriosis 1. Incisional endometriosis (IE) is a rare entity reported in 0.03-1.08%2 of women following obstetric or gynaecological surgeries. Most cases reported in the literature have appeared after caesarean sections and were often clinically mistaken for hernia, abscess, suture granuloma, or lipoma 2.…”
Section: Introductionmentioning
confidence: 99%
“…Incisional endometriosis (IE) is a rare entity reported in 0.03-1.08%2 of women following obstetric or gynaecological surgeries. Most cases reported in the literature have appeared after caesarean sections and were often clinically mistaken for hernia, abscess, suture granuloma, or lipoma 2. The diagnosis is frequently made only after excision of the diseased tissue.…”
Section: Introductionmentioning
confidence: 99%